Single small enhancing CT lesions in Indian patients with epilepsy: clinical, radiological and pathological considerations. Issue 8 (August 1991) - Chandy, M J; Rajshekhar, V; Ghosh, S; Prakash, S; Joseph, T; Abraham, J; Chandi, S M
Abstract : Thirty consecutive Indian patients with focal or generalised seizures and single, small (less than 10 mm), enhancing lesions on CT scans (SSECTL) were studied. Five patients (Group A) were treated with anticonvulsants alone and did not have a biopsy. In ten patients (Group B) a CT guided stereotaxic biopsy of the lesion was carried out and in the remainder (15-Group C) and excision biopsy of the lesion was carried out following CT guided stereotaxic localisation. In all patients in Group B the lesion were reported as "chronic nonspecific inflammation". In seven of 15 patients in Group C the lesions showed a cysticercus with a granuloma and in a further five the pathology was that of a "parasitic granuloma" but the parasite could not be identified. Biopsy did not reveal a tuberculoma or neoplasm in any of the patients. The lesions studied are the same as "disappearing" CT lesions reported in Indian patients, as in 12 of 15 patients in Groups A and B, who could be followed up for more than three months, the lesions had spontaneously disappeared or left calcific residues. It is concluded that in Indian epileptic patients with SSECTL cysticercosis is the commonest aetiology. A treatment protocol for these patients is suggested on the basis of the findings.